A 1D strain-amplitude- and strain-rate-dependent model of super-elastic shape memory alloys for structural vibration control. (June 2020) - Liu, Bo; Li, Binbin; Wang, Sheliang; Liu, Yang; Yang, Tao; Zhou, Yuan
Abstract: The recently increasing interest in using super-elastic shape memory alloys (SMAs) for structural vibration control creates the need for a suitable mechanical model that considers the material's close correlation with the strain amplitude and the strain rate. This paper proposes an improved Graesser-Cozzarelli (G-C) model for predicting the hysteretic responses of the super-elastic SMAs at various strain rates and strain amplitudes. A series of uniaxial tensile tests of super-elastic SMA wires are conducted first, and the effects of the strain amplitude and the strain rate on the characteristic parameters are quantified. Then, based on the original G-C model and experimental test results, an improved version is proposed. The revised model considers the nonlinear hardening behaviour of martensite and divides the complete hysteretic curve into two stages: a loading stage and an unloading stage. Finally, numerical simulations are conducted to evaluate the model's performance in predicting the hysteresis responses at various strain amplitudes and strain rates. High accuracy is realized in all comparisons with the experimental results; thus, the improved G-C model is highly suitable for the simulation of super-elastic SMA-based dampers in applications for vibration control.